A Description and Key of the Eggs and Larvae of Five Species of Fish in the Subfamily Coregoninae - Hinrichs, Michael Arno (University of Wisconsin-Stevens Point, College of Natural Resources, 1979)
The objective of this study was to develop a key to the eggs and larvae of five species of fish representing the three genera in the subfamily Coregoninae. Data were collected from hatchery rearing of fertilized eggs of the lake herring (Coregonus artedii), lake whitefish (C. clupeaformis), bloater (C. hoyi), round whitefish (Prosopium cylindraceum), and the inconnu (Steaodus leucichthys). Seven embryonic stages were described for each species with the exception of the inconnu, for which only the first and seventh stages were described. Lake herring and bloater eggs were inseparable using diameter, color and oil droplet number, as were eggs of the lake whitefish and inconnu. However, diameter was useful in separating the eggs of the lake herring (x=2.0±.03 mm) and bloater (x=1.9±.08 mm) from eggs of the lake whitefish (x=2.8±.20 mm), round whitefish (x=3.2±.17 mm) and inconnu (x=3.1±.10 mm). Eggs of the round whitefish were separated from those of the lake whitefish and inconnu by the orange rather than colorless chorion and higher oil droplet number. Six post-hatching stages were described for each of the five species. At hatching, lake herring and bloater larvae could not be positively identified one from the other, however, the largest dorsal melanophores were generally greater than the width of a myomere in the bloater and less than the width of a myomere in the lake herring. Lake whitefish and inconnu larvae were similar to each other as well as to the lake herring and bloater, however, they were larger and remained larger for comparable stages. Round whitefish larvae had 6-12 oil droplets after hatching, whereas larvae of the other species had one. Lake whitefish larvae had a post-anal myomere count of 16-18, and a subterminal lower jaw which separated it from the inconnu which had 19-22 post-anal myomeres and a terminal lower jaw. Melanophores were often paired across the dorsal finfold in the lake whitefish, irregular anterior to the notch in the dorsal finfold and paired posterior to it in the inconnu, and irregular to alternate in the lake herring, bloater, and round whitefish. The largest of the dorsal stellate melanophores was greater than or equal to the width of a myomere in the round and lake whitefish and less than the width of a myomere in the inconnu. The round whitefish was the only species to exhibit parr markings.